Industrialization in Sarawak : the performance of the electrical and electronic industry in relation to the manufacturing sector - Wong, Muk Ngiik (1999)
This study presents the findings on the current status and performance of the E & E (Electrical and Electronic) industry in relation to the overall manufacturing sector of Sarawak. The performance of the manufacturing sector is assessed using the empirical data from 1970 to 1996 obtained from the Department of Statistics while the analysis of the E & E sector is based on a recently completed survey. Between 1970 to 1996, the manufacturing sector has achieved rapid growth in terms of its share of GDP, contribution to export earnings and employment creation